Size and morphology dependent surface wetting based on hydrocarbon functionalized nanoparticles - Andrew Barron (Journal of Colloid and Interface Science, 2019)
HypothesisThe wetting properties of films created using metal oxide nanoparticles can be controlled through roughness and chemical functionality; however, other variations such as the size and shape of the particles play an important role in improved understanding of the wetting behaviour of these materials.ExperimentsInfrared (IR) spectroscopy and thermogravimetric analysis (TGA) were used to study the chemisorption and grafting density of a carboxylic acid onto the surface of nanoparticles. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) were used to investigate the morphology and roughness of the nanoparticle films. To investigate the wettability and surface energy of the films, static and dynamic contact angle (CA) measurements were used.FindingsSmaller, spherical nanoparticles (<50 nm) were observed to create films that displayed greater surface roughness and showed superhydrophobic properties. By comparison, larger, 135 nm spherical nanoparticles showed reduced surface roughness and displayed water contact angles (WCAs) <150°. Since these particles showed similar carboxylate grafting densities, this suggests that there is a particle size limit above which it is not possible to deposit superhydrophobic films. This study also shows that topographical effects brought about by film roughness can be overcome through increasing the carboxylate grafting density on the surface of the nanoparticles. It was observed that films created using mix shape <50 nm nanoparticles with relatively low surface roughness displayed superhydrophobic WCAs and low hysteresis. These particles also possessed a substantially larger carboxylate grafting density, indicating that the extent of functionalization also has a large bearing on the wettability of the films. Herein, we show that particle size, morphology, and reactivity all play important roles in determining the wettability of nanoparticle films.